Efficacy and tolerability of lithium in treating acute mania in youth with bipolar disorder: Protocol for a systematic review - Duffy, A; Patten, S; Goodday, S; Weir, A; Heffer, N; Cipriani, A (SpringerOpen, 2017)
Background Epidemiological, clinical, and high-risk studies have provided evidence that the peak period for onset of diagnosable episodes of mania and hypomania starts in mid to late adolescence. Moreover, clinically significant manic symptoms may occur even earlier, especially in children at familial risk. Lithium is the gold standard treatment for acute mania in adults, yet to our knowledge, there is no published systematic review assessing lithium treatment of mania in children or adolescents. This is a major gap in knowledge needed to inform clinical practice. Aim As a working group within the ISBD Task Force on Lithium Treatment (http://www.isbd.org/active-task-forces) our aim is to complete a systematic review of the efficacy, tolerability, and acceptability of lithium compared to placebo and other active drugs in treating mania in children and adolescents diagnosed with bipolar disorder. Methods We will include double or single-blind randomized controlled trials in patients aged less than 18 years. No restrictions will be made by study publication date or language. Several electronic databases will be searched along with secondary sources such as bibliographies and trial registry websites for published and unpublished studies. Response rates to lithium compared to placebo or other active drugs will be the primary efficacy outcome. Primary tolerability and acceptability outcomes will be rates of serious adverse events and dropouts, respectively. Secondary outcomes will include rates of remission, severity of manic symptoms at different time points, and incidence of specific adverse events. Discussion Findings from this systematic review are critically needed to inform clinical practice. We should not generalize findings from adult studies, as children and adolescents are undergoing accelerated physiological and brain development. Therefore, efficacy, tolerability, and acceptability of lithium treatment of acute mania in children compared to adults may be very different. This systematic review has been registered in PROSPERO (CRD42017055675).